Groundwater hydrochemistry of a sugarcane cultivation belt in parts of Muzaffarnagar district, Uttar Pradesh, India - Mohammad Muqtada Ali Khan; Rashid Umar (2006)
The Kali-Hindon is a watershed in the most productive central Ganga plain of India. The whole area is a fertile track with sugarcane being the principal crop. Systematic sampling was carried out to assess the source of dissolved ions, impact of sugar factories and the quality of groundwater. Thirty-six samples were collected covering an area of 395 km2. The quality of groundwater is suitable for irrigational purposes but is rich in SO4 which is not best for human consumption. Graphical treatment of major ion chemistry helps identify six chemical types of groundwater. All possible species such as Na–Cl, K–Cl, Na–HCO3, Na–SO4, Ca–HCO3, Mg–HCO3, Ca–SO4 and Mg–SO4 are likely to occur in the groundwater system. The most conspicuous change in chemistry of groundwater is relative enrichment of SO4. The interpretation of data reveals that SO4 has not been acquired through water–rock interaction. The source of SO4 is anthropogenic. Sugar factories alone are responsible for this potential environmental hazard.